The efficacy and safety of panax quinquefolius saponin for heart failure: a systematic review and meta-analysis - Wang, Jing; Chang, Tianying; Liang, Zheng; Cui, Yingzi; Wang, Xiaodan; Wang, Lisha; Jin, Hongguang (Frontiers in Pharmacology, 2025)
BackgroundHeart failure (HF) is a global health concern, affecting millions of individuals worldwide and leading to significant morbidity and mortality. Despite advances in conventional therapeutic strategies, the prognosis for HF patients remains challenging, and there is a constant search for novel therapeutic options. Among these, Panax quinquefolius saponin (PQS) has demonstrated promising pharmacological properties that may benefit HF. However, the efficacy and safety of PQS for HF have not been comprehensively evaluated.ObjectiveThis systematic review and meta-analysis aim to provide a more reliable estimation of the efficacy and safety of PQS for HF. This will help clinicians make informed decisions regarding the potential use of PQS in managing HF patients.MethodsWe comprehensively and systematically searched for published randomized controlled trials (RCTs) in the following eight electronic databases: PubMed, Cochrane Library, EMBASE, Web of Science (WOS), China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), Wanfang Data, and China Biology Medicine Database (CBM) from database inception to March 2024. The Cochrane risk of bias (ROB 2.0) assessment tool was used for quality assessment, and Review Manager (RevMan, version 5.4) was used for meta-analysis. Mean difference (MD), 95% credible interval (CI), and relative risk (RR) estimates were calculated under a random-effects model. We also used GRADE profiler (GRADEpro, version 3.6) to analyze the quality of outcomes. In addition, the protocol has been registered in International Platform of Registered Systematic Review and Meta-analysis Protocols (INPLASY) under registry number 202440050.ResultsThis study included nine RCTs involving a total of 952 patients with HF. The results of a meta-analysis under a random-effects model showed that adjuvant PQS therapy significantly increased LVEF (MD = 6.23, 95% CI [4.35, 8.12], P < 0.00001), 6MWTD (MD = 25.26, 95% CI [8.23, 42.30], P = 0.004), and decreased BNP/NT-pro-BNP (MD = −187.94, 95% CI [−267.20, −108.67], P < 0.00001), LVEDV (MD = −22.83, 95% CI [−42.79, −2.87], P = 0.02), LVEDD (MD = −4.76, 95% CI [−5.77, −3.74], P < 0.00001), and LVESV (MD = −11.86, 95% CI [−19.89, −3.83], P = 0.004) in patients with HF.ConclusionThe evidence provided by this systematic review suggests that adjunctive PQS therapy for HF can improved clinical efficacy and holds potential advantages in improving cardiac function and increasing exercise tolerance. However, given the limitations inherent in this review, the conclusions of this study should be interpreted cautiously. Therefore, in clinical practice, it is recommended that physicians tailor treatment strategies according to the specific circumstances of individual patients.Systematic Review registrationhttps://inplasy.com/?s=202440050